ESRA19-0207 The effect of transversus abdominis plane block combined with intravenous analgesia on perioperative analgesia and recovery in abdominal colorectal surgery patients. (30th August 2019) - Zhou, H; An, E
Abstract : Background and aims: To assess the efficacy of preoperative transversus abdominis plane block (TAPB) on perioperative analgesic effect and recovery in patients with abdominal colorectal surgery. Methods: 80 patients scheduled to undergoing abdominal colorectal surgery were randomly divided into two groups (group P and group R), with 40 cases in each group. Ultrasound-guided TAPB was practiced after general anesthesia in Group R with 0.375% Ropivacaine, capacity of 0.3 ml/kg per side, and not given processing to patients in group P. Sevoflurane concentration was maintained at 0% to 2% intraoperatively. Entropy index was maintained 40–60 intraoperatively and kept SPI ≤50. Sufentanil was added 0.1ug/kg per time according to SPI. The two groups were implemented PCIA after surgery. The sevoflurane usage in the intraoperative and sufentanil usage in the perioperative, postoperative VAS score at five time points, adverse reactions, ambulation and length of hospital stay and patients' satisfaction of two groups were analyzed. Results: Compared with group P, the usage of sufentanil intraoperative and 2h and 6h after surgery of Group R was significantly lower than that of group P. The time to gastrointestinal function recovery and patients' first ambulation of Group R was in advance, and insufficient analgesia cases are lesser than Group P (p<0.05). Conclusions: Ultrasound-guided TAPB can provide safe postoperative analgesia and reduce postoperative pain in patients with abdominal colorectal surgery, beneficial to the rehabilitation of patients.